SELEKSI PENGANGKATAN PEGAWAI NEGERI SIPIL DALAM JABATAN STRUKTURAL - Ajib Rakhmawanto (Jurnal Manajemen Kepegawaian, 2007)
The new paradigm of Indonesia civil service operates by adhering to the standard of appointing people with amerit standard. For a long time, appointing people on the basis of merit was basic principle of the promotingemployees in Indonesia civil service system. PP Nomor 100 Tahun 2000 endorcement of the principlessof openness, fairness, competition and selecting the best. This regulations requires using examinations forentry level positions. Unfortunately, some local goverments have not taken the requirement even futher byusing competition as a mechanism to fill upper-level positions as well.Key words: Civil Service Performance, merit system, competence, proffesional officer